Comparison of Molecular and Parasitological Methods for Diagnosis of Human Trichostrongylosis - Pandi, Mehdi; Sharifdini, Meysam; Ashrafi, Keyhan; Atrkar Roushan, Zahra; Rahmati, Behnaz; Hajipour, Nayereh (Frontiers in Cellular and Infection Microbiology, 2021)
Human trichostrongyliasis is a zoonotic disease that is prevalent among rural populations in some countries. This study was performed to evaluate various parasitological methods and polymerase chain reaction (PCR) for the diagnosis of human trichostrongyliasis. A total of 206 fresh stool samples were collected from residents of endemic villages of Northern Iran. All samples were examined using conventional parasitological methods, including wet mount, formalin ethyl acetate concentration (FEAC), agar plate culture (APC), Harada–Mori culture (HMC), and Willis, along with the PCR technique. Among the total of 206 individuals examined, 72 people (35%) were found infected with Trichostrongylus species using combined parasitological methods. By considering the combined results of parasitological methods as the diagnostic gold standard, the Willis technique had a sensitivity of 91.7% compared with 52.8% for the APC, 40.3% for the HMC, 37.5% for FEAC, and 5.6% for the wet mount technique. The diagnostic specificity of all the parasitological methods was 100%. Furthermore, the PCR method detected Trichostrongylus spp. DNA in 79 fecal samples (38.3%) with a sensitivity of 97.2% and a specificity of 93.3%. According to the current findings, the Willis method was more sensitive than are the other parasitological methods in the diagnosis of human trichostrongyliasis. However, the PCR assay was more sensitive and more reliable in the detection of human trichostrongyliasis in comparison with the parasitological methods.